PENGARUH GOOD CORPORATE GOVERNANCETERHADAP AUDIT REPORT LAG DENGAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN SEBAGAI VARIABEL MODERASI - Hilendri, Bq. Anggun; Bambang, Bambang; Yulia, Yana (Jurnal Aplikasi Akuntansi, 2017)
The demand for transparency is quite high since Indonesia is mired in the economic crisis. In fact, this situation is very understandable since a very good level of transparency ascertained the parties’ concerned regarding accountability of management. Transparency of the company's financial statement is reflected on the audit and the timeliness of financial reporting. This study aims to examine the influence of good corporate governance on audit report lag with the timeliness of financial statement submission as a moderation variable. Independent variables used in this study are board of commissioners, independent commissioners, audit committees, and public accounting firms, with timeliness of financial statement submission as the moderating variable, and audit report lag as dependent variable. The population in his research is 100 companies listed in Kompas 100 stock index. Pursuant to purposive sampling technique, this study obtained 84 companies for oneyear observation, which is the year of 2015. The result of the study indicate that board of commissioner have negative effect to audit report lag, while independent commissioner, audit committee, and the size of public accounting firm has no influence on audit report lag. The results also show that the timeliness of financial statement submission could not be the moderator on the relationship between board of commissioner, independent commissioner, audit committee and public, accountant firms with audit report lag.